Sputum smear positivity grade and chest X-ray findings in tuberculosis: A cross-sectional study - R. Behzadmehr (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Despite many advances in the diagnosis, screening, and rapid treatment of tuberculosis, it is still a public health concern in the world. Due to the importance of this issue in diagnosis and reduction of transmission of infection and treatment of the disease especially where this study is conducted due to the high prevalence of tuberculosis, this study was done to determine The relationship between sputum smear positivity grade and chest X-ray findings in pulmonary tuberculosis patients in a hospital in southeast of Iran. This cross-sectional study was performed on all patients with pulmonary TB referencing the health centers in Zabol city, southeast of Iran from 1 January 2015 to 30 December 2020. Sputum smear and radiographic findings of the chest X-ray were evaluated. Data was collected using a form of information and finally analyzed by SPSS 22. Out of 101 patients examined in the present study, 71 were women and 30 were men. The mean age of the patients was 62.68 ± 13.61 years. The frequency of opacity in patients with grades 1, 2, and 3 was 71.4, 78.5, and 76.5%, respectively. Frequency of cavitation in patients with Grade 1, 2 and 3 was 11.5%, 28.5% and 52.9% respectively (P value 0.001). The frequency of reticulonodular presentations in patients with grade 1, 2, and 3 was 24.2, 7.1, and 0%, respectively.  In general, the results of this study showed that, with increasing grading of smears (1+, 2+, and 3+), the frequency of cavitation presentation increased significantly and the frequency of reticulonodular presentations decreased significantly. In general, the results of this study showed that, with increasing grading of smears (, the frequency of Cavitation presentation increased significantly and the frequency of reticulonodular presentations decreased significantly. The findings of the present study can help physicians better diagnose TB.